Correlation between expression of immunohistochemical markers and morphology in lung neuroendocrine neoplasms - Chytaieva , Halyna (The Ukrainian Scientific Medical Youth Journal, 2022)
lung neuroendocrine neoplasms embrace rather heterogeneous and rare malignancies which are usually characterized by nonspecific, “blurred” clinical signs thus complicating correct diagnosis or seriously delays it. Pulmonary neuroendocrine neoplasms accurate diagnostics and classification need to be improved. Histological examination should be supplemented by immunohistochemical tests to verify the neuroendocrine component, assess proliferative index of tumor cells, and confirm its bronchopulmonary origin. Immunohistochemistry is especially important in case of small or crushed biopsies, which account more than 50% of all specimens in lungs neuroendocrine neoplasms. Modern classification of lung neuroendocrine neoplasms and their grading are based on morphological criteria. Immunohistochemical markers expression is quite variable in different histological subtypes of bronchopulmonary neuroendocrine neoplasms, often data are descriptive, and correlation with morphology is studied insufficiently. The aim of this study was to define any significant correlation between different immunohistochemical markers expression, necrosis, proliferative index (Ki-67 ratio), and tumor grade in broncho-pulmonary neuroendocrine neoplasms. Histological blocks of lung neuroendocrine neoplasms from 113 unique patients (36 resections and 77 biopsies (54.5% of biopsies appeared to be small or crushed) were used in this study. The sample comprised 91 male and 22 female patients; the mean age was 59.2, CI 95% (56.9–61.4) years (from 19 to 77 years). Histological examination (including neuroendocrine morphology, necrosis, and grade) was provided in all cases. Also, immunohistochemistry, using Chr A, Syn, CD56, TTF-1, CK7, and Ki-67 before chemotherapy was performed. All morphological and immunohistochemical data were assessed by two different independent pathologists without the access to patient’s clinical data. All the observations were classified based on 2021 WHO Thoracic Tumors Classification. The sample was censored. We used nonparametric statistics (Spearman’s rank correlation) for this study. In was found that Chr A expression strongly (p<0.05) correlated with immunohistochemical markers of primary lung malignancies (TTF-1 and CK7) that are mainly expressed in highly and moderately differentiated neuroendocrine neoplasms. Also, positive expression for TTF-1 and CK7 correlated with each other (p<0.01). There was a strong negative correlation (p<0.05) between Chr A staining and necrosis presence and it’s severity; between Chr A expression and tumor cells proliferation (Ki-67 ratio) (p<0.01); and between Chr A labeling and tumor grade (p<0.01). The correlation of immunohistochemical markers expression with necrosis, Ki-67 ratio and tumor grade was significant only for Chr A. All other tested options, for other markers were not statistically significant. It was defined that decrease or loss of Chr A expression reliably indicates tumors progression. Chr A expression can be used as an additional tool for grading of lung neuroendocrine neoplasms.